To Foundations of General Theory Relativity (Global Journal of Science Frontier Research, 2023)
It is shown that the foundations of the generally accepted theory contain a number of contradictory and unfounded statements The geometric properties of the three-dimensional Riemannian space are successively described It is shown that this space is locally Euclidean The metric tensor can be algebraically diagonalized In this case all diagonal elements are equal to each other and differ from unity by a function of coordinates which is called the gravitational potential It is shown that this function is a solution of the differential equation of potential theory If this solution is such that the potential can be represented by equipotential surfaces then the trajectory of free motion of a material particle lies on this surface The trajectory on the surface is a geodesic line determined by the initial conditions The numerical value of the potential on the surface is included in the definition of the maximum possible speed on this surface that is a constant equal to the speed of light in vacuum is multiplied by a value less than one determined by the value of the potential
Keywords: general theory relativity; Riemannian space; pseudo-Riemannian space; gravitational potential